Conceptual Methodology For Requirement Engineering Based on GORE and BPM - Imam M. Shofi, Ahmad Nurul Fajar , (PROCEEDING IC-ITECHS 2014, 2014)
The main measure of the success of a software system is the degree to which it meets itspurpose. Requirement Engineering (RE) is a process for discovering the purpose.Nowdays, the complexity of e-governemnt applications is grown significantly in the government environment.E-government applications should be developed based on regulations in order to achieve the goal model of government entitties. However, the goal model could not used directly to identify the features of applications.In order to solve this problem,this paper presents and proposed conceptual methodology for requirement engineering based on GORE and BPM Alignment.It can support the phase for identify features of applications. In order to support this phase, we align goal model and business process model.This conceptual methodology consists of four methods, there are (1)Method for convert document regulations to goal model, (2).Method for convert goal model into business process model, (3).Method for convert business process model into feature model,and (4).Method for convert feature model to orthogonal variability model